Corporate Governance Effects on Accounting Performance: Timely and Untimely Companies in Submitting Financial Statements - Iswadi Bensaadi; Nur Asyiah (PT Mattawang Mediatama Solution, 2022)
This research analyzes the effect of institutional ownership, managerial ownership, board of directors, and board of commissioners on the accounting performance of timely and untimely companies in submitting financial statements. This research also analyzes different effects of institutional ownership, managerial ownership, board of directors, and board of commissioners on accounting performance between timely and untimely companies in submitting financial statements in Indonesia during 2016-2020. This research uses panel data collected with documentation techniques and used multiple linear regression panel data. The samples used are 71 companies divided into two sample groups, namely 40 timely companies submitting financial statements and the rest 31 untimely companies submitting financial statements. The results indicates that institutional ownership positively and significantly influences the accounting performance of timely and untimely companies in submitting financial statements. Managerial ownership, board of directors, and board of commissioners has no significant positive effect on the accounting performance of timely and untimely companies in submitting financial statements. Furthermore, this research does not find different effects of institutional ownership, managerial ownership, board of directors, and board of commissioners on the accounting performance of timely and untimely companies submitting financial statements.